Pemberdayaan Peternak Itik Melalui Pakan Fermentasi Dalam Upaya Menghasilkan Telur Rendah Kolestrol (Teresol) Di Desa Bate Puteh Kecamatan Langsa Lama Kota Langsa: - Rosmiati Rosmiati; Kiagus Muhammad Zain Basriwijaya; Saragih F.H; Ilham F (COMSEP: Jurnal Pengabdian Kepada Masyarakat, 2021)
Langsa City is currently one of the centers for laying ducks. One of the sub-districts currently developing laying duck farming is Langsa Lama District, Langsa City. In the laying duck cultivation business, there are several problems faced by breeders, including the handling of seeds in general is still in a simple/traditional manner. One of them is a nursery method that has not been touched by technology so it takes a long time to get laying duck seeds. Teresol is a feed mixing technology by adding 3% tea leaf powder to conventional feed. The addition of tea is very efficient because it does not reduce the production of the ducks, because if it is more than 3% then the ducks will experience quite a lot of energy disassembly and result in a decrease in production. In this community service, farmers are first given counseling about fermented feed, how to make it and the benefits felt for farmers by increasing the productivity of duck eggs that are kept. After the training activities with demonstrations were carried out, an evaluation was carried out by distributing questionnaires to the participants to see the level of knowledge of the participants before and after the activity. Duck farmers can increase family income and welfare by producing low-cholesterol eggs with high selling value.